2020
DOI: 10.3390/pathogens9040246
|View full text |Cite
|
Sign up to set email alerts
|

Cold Exposure-Induced Up-Regulation of Hsp70 Positively Regulates PEDV mRNA Synthesis and Protein Expression In Vitro

Abstract: Porcine epidemic diarrhea (PED) is a highly contagious, intestinal infectious disease caused by porcine epidemic diarrhea virus (PEDV). PEDV as an emerging and re-emerging epizootic virus of swine causes substantial economic losses to the pig industry in China and other countries. In China, the occurrence of PED shows significant seasonal variations, usually outbreak during the winter season. The epidemic characteristics of PED may be highly correlated with the changes of ambient temperature. However, molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
3
3
0
Order By: Relevance
“…Although the present study was not designed to elucidate seasonal differences in the estimated quantity for PEDV genome in the different parts of the world, the results suggest a higher frequency of detection and viral loads during the winter, while it was lower in summertime ( S1 and S2 Tables). These results are consistent with the observation that PEDV is more stable in cold environments [ 50 ] and has a lower incidence of clinical diarrhea cases at farms during the summer season [ 51 ].…”
Section: Resultssupporting
confidence: 92%
“…Although the present study was not designed to elucidate seasonal differences in the estimated quantity for PEDV genome in the different parts of the world, the results suggest a higher frequency of detection and viral loads during the winter, while it was lower in summertime ( S1 and S2 Tables). These results are consistent with the observation that PEDV is more stable in cold environments [ 50 ] and has a lower incidence of clinical diarrhea cases at farms during the summer season [ 51 ].…”
Section: Resultssupporting
confidence: 92%
“…They concluded that HSP70 positively regulated PEDV mRNA synthesis and protein expression. These results are similar to our results in the correlation between HSP70 and PEDV replication [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although the present study was not designed to elucidate seasonal differences in the estimated quantity for PEDV genome in the different parts of the world, obtained results suggest higher frequency of detection and viral loads during the winter, while it was lower in summertime (S1 and S2 Tables). These results are in line with the fact that PEDV is more stable in cold environments [50] and has lower incidence of clinical diarrhea cases at farms during the summer season [51].…”
supporting
confidence: 83%